Design of simulated moving bed and Varicol processes for preparative separations with a low number of columns - Pais, Luís S. (2003)
Simulated moving bed (SMB) chromatography has received significant attention in the last decade, particularly as regards the production of very valuable products, such as enantiomerically pure pharmaceutical compounds. Recent applications in the pharmaceutical industry use SMB systems containing a low total number chromatographic columns, usually four to eight. This paper deals with the modeling and simulation of SMB systems with only four, five and six columns. In particular, two modeling strategies, the equivalent true moving bed and the real SMB models, are compared for these units in terms of separation regions and system productivity. Also, the recently proposed Varicol process is analyzed and compared with the classical SMB operation, and the advantages of this new operation mode are shown for systems using a low number of columns.